Strategi Marketing Public Relations Di The Axana Hotel - Tiara Fadilla Putri Trisnadi; Hijriyantomi Suyuthie (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This research is motivated by problems found in the Public Relations Strategy at The Axana Hotel, measured from three indicators, namely Publications, Media Identity and Public Service Activities. Problems are still found related to publications on The Axana Hotel's social media which do not always receive high attention, Identity Media which is still under the shadow of the collapse of the Ambacang Hotel during the Padang earthquake in 2009, Public Service Activities implemented by The Axana Hotel also implemented in other hotels. The purpose of this research is to find the Public Relations Marketing Strategy at The Axana Hotel. This research is descriptive research with qualitative methods. Data collection techniques were carried out using observation, interviews and documentation methods. There were 3 informants in this study, using a purposive sampling method. This research uses the SWOT analysis technique through identifying Strengths, Weaknesses, Opportunities and Threats. The results of this research are strategies that can be used for Marketing Public Relations at The Axana Hotel which are reviewed based on 3 indicators including publications, identity media and public service activities.